The Mediating Effects of Coping Style on the Effects of Breath Count Mindfulness Training on Depressive Symptoms among International Students in China - Simeng Gu; Yawen Li; Fei Liang; Rou Feng; Zhi Zeng; Fushun Wang (Neural Plasticity)
Mindfulness training has gained popularity in the scientific field and has been proposed as an efficient way for emotional regulation. Mindfulness-based cognitive therapy (MBCT) is designed especially for depressive people in reducing risk of depression relapse and is recommended in national guidelines as a treatment choice for relapse prevention in recurrent depression. The aim of the current study was to investigate the effects of mindfulness training on depressive symptoms of international students and probe into the mediating role of mindfulness in stressful events and depression. In addition, we introduced a new kind of mindfulness training, the breathing exercise-based mindfulness training, which is based on the integration of Buddhism and Daoism. Self-report questionnaires assessing the coping style, abnormal depressive behavior, and stressful live events were completed in 260 international students in China (mean age=21.4 years). The results showed that (1) many international students showed depression symptoms, (2) stressful life events play a completely mediating role in the initiation of depression and anxiety, and (3) mindfulness training for 8 weeks significantly reduced the depressive symptoms, and it was also related to a positive coping style. This study has certain theoretical significance in exploring the mechanism of the occurrence and development of depression among international students and provides useful tools for this special group of international students. In addition, the international students can also learn Chinese culture through the training. These findings indicate that mindfulness training and positive coping style are interrelated with treating depressive symptoms for international students.